Perbandingan Algoritma Naïve Bayes, Svm Dan Trees J48 Pada Pengenalan Pengaruh Suara Konsonan Terhadap Vokal - Muhammad Makmun Effendi (Jurnal SIGMA, 2021)
Sound is the most basic communication tool that humans have. Technological developments are increasingly high so that human needs in living his life with practical and automatic, then the development of technology toward the field biometrica. This study was conducted to determine whether between the male and female voice types can be recognized by recording the consonant letters that have been influenced by vowels, by comparing the Naive Bayes algorithm, SVM algorithm, and J48. Research methods used in building this voice recognition system based on consonants that have been influenced by vowels by comparing the Naïve Bayes, SVM and Trees J48 algorithms. This is done to find out from the two algorithms compared which are better at recognizing consonant sounds that have been affected by the vowel sound. Keywords : Sound, Naïve Bayes, SVM and Trees J48